STRATEGI KEBIJAKAN PEMBANGUNAN KEMARITIMAN DALAM KERANGKA PENINGKATAN INVESTASI NASIONAL - M. Rizal Taufikurahman; Dudi Setiadi Hendrawan (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
Maritime development effort can not be separated from the development of strategic environments that include the supporting economic environment both on a regional scale, national, even at the global level. The aim of this study is (1) mapping out the opportunities and threats of the maritime sector in Indonesia based on the dynamics of the domestic and global environment, and (2) to formulate the maritime development policy strategy within the framework of national investment development. The method used is SWOT analysis. The results of the study indicate that opportunities that can be utilized for the benefit of domestic development can be seen from the potential of marine in the territory of Indonesia. The threat of the maritime sector comes from internal and external. The internal factors of inequality and disparity gap of development. The external factors threats are border disputes and lack of law enforcement, defense and security controls in border areas. The recommended policy suggested that government needs to do maritime-oriented development, connectivity through strengthening logistics and marine economy, economic development about prosperity approach and security, controlling related with the nation's authority and maritime, and reorientation of development towards maritime development with the achievement of planting more progressive capital.